The impact of inter-union conflicts on industrial harmony: The case of tertiary health institutions in Cross River State, Nigeria - Bassey Antigha Okon,; Ojua Takim Asu,; Archibong Esther Patrick,; Bassey Umo Antigha, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
The study was carried out to determine the impact of inter-union conflicts on industrial harmony. University of Calabar Teaching Hospital and Federal Neuro-Psychiatric Hospital Calabar were the only tertiary health institutions in Nigeria’s Cross River State and the 2575 total staff strength of the two organizations was the study population. A total of 266 subjects was randomly sampled. Pearson Product Moment Correlation test was conducted to test the null hypothesis and it was established that there was significant influence of inter-union conflicts on industrial harmony in the study case. Recommendations to reduce the inter-union conflicts and enhance industrial harmony include, among others, the removal of salary disparity among unions, and the review of law and working conditions.